Una representación de la crisis de la unión dinástica: los cargos diplomáticos en Roma de Francisco de Rojas y Antonio de Acuña (1501-1507) - Serio, Alessandro (Cuadernos de Historia Moderna, 2007)
This essay is part of a research on Spanish presence in Rome between the end of XV and the first decades of XVI century. Giving account of the interest recently arisen on the relationships among the Monarquía Católica and the Papacy in Early Modern period, it has been our intention to look at the first moments of these relationships, going back to the years past the Dinastic Union (1469) and looking for elements that could express their complexity. The presence, at the same time, of more than one “Spanish” ambassador and the participation to those relationships of a high number of individuals (with their own social and relational networks articulated in both the Spanish and Italian peninsulas) suggests the existence of various relational levels and stresses the importance of debating the interpretations currently proposed by American historians such as Thomas Dandelet and Michel Levin.